Match performance analysis of collegiate basketball teams in Nigeria - Abimbola, T. I.; Dominic, O. L.; Alabidun, M.; Seidina, I. Y. (Journal of Human Sport & Exercise, 2018)
Background: Match statistics is valuable to coaches, team managers and board room executives of basketball teams for analysis of players´ performance, scouting, team selection and operations. The objectives of this study were to measure, analyze skillsprofile and rank the performance of collegiate basketball teams in Nigeria. Methodology: Descriptive comparative research design was used for this study. The population was 79 players consisting of the best eight teams that were purposively selected basedon the current performance ranking at various collegiate games in Nigeria. Standardized application software (MBT/FIBA Europe SmartStats for basketball version-2.6.1) was used to box-score data collection. Data analyses were conducted using the SPSS version-20.0 software. Descriptive statistics of percentage and mean were used for analysis of shots and inferential statistics of One-way ANOVA was used to analyze the differences in shots performance among the teams with p <= 0.05 for statistical significance. Findings: Some of the teams were excellent in certain performance variables but ranked below the top three. There was no significant difference in the scoring of the 2-point Field Goal F (7, 78) = .681 p = .688 and 3-point Field Goal F (7, 78) = .834, p = .563 among collegiate basketball teams in Nigeria. Conclusion: Rather than individual talent, team success comes from combination of talent, coaching skills, strategy, team fitness and spirit. Utilizing basketball analytics is vital for identifying team strength and weaknesses for focused performance improvement of collegiate basketball in Nigeria.